Drifting while stepping in place in old adults: Association of self-motion perception with reference frame reliance and ground optic flow sensitivity. (7th April 2017) - Agathos, Catherine P.; Bernardin, Delphine; Baranton, Konogan; Assaiante, Christine; Isableu, Brice
Highlights: Stepping in place maximizes optic flow effects, especially in old adults. Drifting when stepping in place reveals poorer egocentric self-motion perception. Poor egocentric self-motion perception is linked to greater optic flow sensitivity. A motor index of visual reference frame reliance is proposed. Visual reference frame reliance for self-motion perception is shown from middle-age. Abstract: Optic flow provides visual self-motion information and is shown to modulate gait and provoke postural reactions. We have previously reported an increased reliance on the visual, as opposed to the somatosensory-based egocentric, frame of reference (FoR) for spatial orientation with age. In this study, we evaluated FoR reliance for self-motion perception with respect to the ground surface. We examined how effects of ground optic flow direction on posture may be enhanced by an intermittent podal contact with the ground, and reliance on the visual FoR and aging. Young, middle-aged and old adults stood quietly (QS) or stepped in place (SIP) for 30 s under static stimulation, approaching and receding optic flow on the ground and a control condition. We calculated center of pressure (COP) translation and optic flow sensitivity was defined as the ratio of COP translation velocity over absolute optic flow velocity: the visual self-motion quotient (VSQ). COP translation was more influenced by receding flow during QS and by approaching flow during SIP. In addition, old adults drifted forward while SIP without any imposed visual stimulation. Approaching flow limited this natural drift and receding flow enhanced it, as indicated by the VSQ. The VSQ appears to be a motor index of reliance on the visual FoR during SIP and is associated with greater reliance on the visual and reduced reliance on the egocentric FoR. Exploitation of the egocentric FoR for self-motion perception with respect to the ground surface is compromised by age and associated with greater sensitivity to optic flow.